Productivity Improvement Strategy Analysis Palm Oil in Sumatra Province 2011-2021 - Ardi Afrizal; Agus Santoso; Rian Dani (Universitas Batanghari Jambi, 2022)
This study uses a weighted index model and a productivity model where Aceh Province is the province with the highest weighted ranking value with a weighted value of 2.06, meaning that Aceh Province to obtain 1 ton of palm oil requires an average area of 2.06ha. Meanwhile, North Sumatra Province is the province with the lowest weighted index value when compared to other Sumatra Provinces, namely with a weighted value of 3.62, meaning that to obtain 1 ton of palm oil, an area of 3.62 Ha is needed. The highest productivity of palm oil production is in Aceh Province at 49.16% while the lowest palm oil production productivity is in North Sumatra Province at 27.98%. The strategy to increase the added value of palm oil production in Sumatra Province is through mapping of smallholder and company palm oil production areas, regulations for the sustainability of palm oil production, provision of subsidized fertilizer assistance for oil palm farmers, especially smallholder farmers and supervision and assistance to oil palm farmers in selecting seeds and processing land.